Elaboration and realisation of innovative projects by “Tomskneftekhim” Ltd. and Institute of Catalysis of SB RAS in frames of special economic zone - Mayer E. A. Eduard Aleksandrovich; Dudchenko V. K.; Kolkov K. M.; Arkatov O. L.; Zakharov V. A.; Nikitin V. E.; Mikenas T. B. (2010, 2010)
Title screen